A novel approach based on X-ray fluorescence and photon attenuation to the analysis of soils for forensic investigation - Luiz Fernando Pires; Luis Valério Prandel; Sérgio da Costa Saab; André Maurício Brinatti (Revista Brasileira de Ciência do Solo, 2022)
ABSTRACT Use of soil in forensic science is related to its several chemical, physical, and biological properties associated with its capacity to adhere to different materials and surfaces. Forensic soil experts and police investigators have been using soil samples as an aid in criminal investigations. Soils can act as fingerprints because they present contrasting physical, chemical, biological, and mineralogical properties. However, depending on the analytical tools utilized to characterize the soil, differentiating the samples when they have similar properties might be impossible. Thus, soil utilization as a fingerprint material requires increasing the number of variables measured as well as the accuracy and precision of the measurements. This study presents the feasibility of methods based on X-ray fluorescence (XRF) and radiation interaction parameters to discriminate soils for forensic investigations. Analyses of soil particle size, elemental composition (XRF), mass attenuation coefficient (μ), atomic (σa) and electronic (σe) cross-sections, effective atomic number (Zeff), and electron density (Nel) were carried out to evaluate the potential of nuclear parameters to differentiate soils. Ten different soil types collected at 0.00-0.05 m layer were studied. The radiation interaction parameters were obtained through the XCOM computer code, while the experimental measurements were carried out by the traditional gamma-ray attenuation method utilizing the radioactive sources of 241Am and 137Cs. The results showed that the soils presented broad differences in terms of clay, silt, and sand contents as well as in the major oxides. These differences influenced the radiation attenuation properties as verified through the multivariate analysis. For the lowest photon energy studied (10 and 30 keV), σe was the most interesting parameter to discriminate the soils. For energies above 59.5 keV, Zeff and Nel were the most important parameters. Good agreement was found between the calculated and measured parameters. The findings of this study indicate that radiation interaction parameters have great potential for crime scene investigation providing new parameters for better discrimination of soils. The main advantage of the method presented here is that it is fast, easy to implement, does not require powerful computers, and the XCOM code can be run online at the NIST (National Institute of Standards and Technology, USA) website.